Spatio–temporal evolution and factors of climate comfort for urban human settlements in the Guangdong–Hong Kong–Macau Greater Bay Area - Zhou, Chunshan; Zhang, Dahao; Cao, Yongwang; Wang, Yunzhe; Zhang, Guojun (Frontiers in Environmental Science, 2022)
This study used both temperature-humidity and wind efficiency indices at three time-scale resolutions (year, season, and month) for the first time, to analyze the spatio–temporal evolution of urban climate comfort in the Guangdong–Hong Kong–Macau Greater Bay Area (GBA). The main factors affecting human-settlement climate comfort were elucidated and the annual changes in both indices used in the study area exhibited fluctuating growth from 2005 to 2020. Moreover, the annual growth of the temperature-humidity and wind efficiency indices in the southern cities of the GBA was relatively fast. In contrast, the annual growth of these indices in the northern cities of the GBA was relatively slow. Overall, the climate of the human-settlement environments in the GBA was the most comfortable in spring and autumn, and summer and winter were characterized by hot and cold climate conditions, respectively. We did not identify any prominent change in the climate comfort of spring and autumn from 2005 to 2020; however, the climate comfort degree deteriorated in summer and ameliorated in winter. On a monthly scale, the human-settlement environments in the GBA were the coldest in December and the hottest in July. The urban human settlements were cold in January and February, hot in May, June, August, and September, and the most comfortable in March, April, October, and November in 2020. We analyzed the factors affecting the climate comfort of human-settlement environments in the study area and found that elevation, gross industrial production, population scale, and construction land area were the most influential parameters. Notably, the impact of natural factors on the climate comfort of human-settlement environments was more significant than that of anthropogenic factors. Moreover, the related factors affected the temperature-humidity index more strongly than the wind efficiency index. Overall, our results provide data-driven guidelines for improving the climate comfort of urban human settlements in the GBA.